English Grammar Teaching Strategies in a Limited-Resource Junior High School - Karina Karina; Andi Tenrisanna Syam; Madehang Madehang; Devi Ismayanti (KARIWARI SMART : Journal of Education Based on Local Wisdom, 2026)
Grammar instruction remains a fundamental component of English as a Foreign Language (EFL) learning. However, empirical studies that document how grammar-teaching strategies are implemented in junior high school classrooms, particularly in limited-resource contexts, remain relatively limited. This study aims to analyze the grammar teaching strategies implemented by English teachers at SMP Negeri Satap 2 Kolaka Utara. A qualitative research design was employed involving three English teachers selected through purposive sampling. Data were collected through classroom observations and semi-structured interviews and analyzed using the interactive model of data analysis, including data reduction, data display, and conclusion drawing. The findings reveal that teachers implemented several grammar-teaching strategies, including interactive and student-centered activities, group-based learning, the integration of learning media and technology, contextual instruction, and adaptive teaching practices to address classroom challenges. These strategies encouraged greater student participation, supported students’ understanding of grammatical structures, and fostered more positive attitudes toward grammar learning. The study also shows that teachers demonstrated pedagogical flexibility by adapting instructional practices to students’ needs and to the limitations of available learning resources. This study contributes to the literature on EFL pedagogy by providing empirical evidence that communicative, collaborative, and contextual grammar-teaching strategies can be effectively implemented even in schools with limited instructional facilities. The findings highlight the importance of teachers’ pedagogical creativity and adaptability in supporting effective grammar instruction and improving student engagement in EFL classrooms.